Continuity properties on p for p-Laplacian parabolic problems - Bruschi, Simone Mazzini [UNESP]; Gentile, Claudia Buttarello; Teixeira Primo, Marcos Roberto (Pergamon-Elsevier B.V. Ltd, 2010)
In this work we obtain some continuity properties on the parameter p at p = 2 for the Takeuchi-Yamada problem which is a degenerate p-Laplacian version of the Chafee-Infante problem. We prove the continuity of the flows and the equilibrium sets, and the upper semicontinuity of the global attractors. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: p-Laplacian; Laplacian; Continuity on p; Equilibria; Attractors